The Problem of Polish (Self-)Stereotypes. The Perspective of Applied Cultural Studies - Rotengruber, Przemysław (Journal of Applied Cultural Studies, 2016)
The aim of the study is to analyse the stereotype of the Pole in the context of the Applied Cultural Studies perspective. Four basic areas of research can be discerned: other people’s variable associations concerning Poles; other people’s prejudices and generalizations that influence their attitude towards Poles; the results of Poles’ self-evaluation made on the basis of their current experience; the “social frameworks of memory” which shape the Poles’ ideas concerning their place in history. Since the purpose of this investigation is to reconstruct the mechanism of self-stereotyping, which involves scholars as much as the society they serve, contingent feelings about their situation are of secondary importance.